Pemberdayaan Anak Yatim Melalui Pendayagunaan Dana Zakat, Infaq, dan Shadaqah Pada Lembaga Amil Zakat Yatim Mandiri Surabaya - Andik Eko Siswanto; Sunan Fanani (Universitas Airlangga, 2017)
The aims of this research is to find out the role of utilizing zakat, infaq and shadaqa on the empowerment of orphans in amil zakah institution of Yatim Mandiri Surabaya. The research method used in this research is descriptive qualitative with the case study method. In collecting the data, in-depth interview and direct observations had been done on the informants. Journals, text books, and other literatures are also used for the secondary data. This research found out that the utilization of zakat, infaq and shadaqa fund had a role in empowering the orphans through Mandiri Entrepreneur Center (MEC) program. The empowerment given on the orphans are in the form of education and entrepreneurship training while living in a dormitory. The development of this empowerment can be seen clearly with enhancements in academic independence, religion independence and economic independence.